Undertreatment of pain and low use of opioids in Latin America (2018)
Pain is highly prevalent among the adult Latin American population. However, many patients with moderate to severe pain do not have access to effective pain management with opioids due to limited access to healthcare, overuse of nonopioid analgesics, regulatory barriers and lack of appropriate information about opioids. There is scarce training on use of opioids among physicians and other healthcare providers, which leads to misconceptions, mainly related to a fear of prescribing opioids. Although opioids are safe and effective drugs for the treatment of moderate to severe chronic pain, the use of opioids in Latin American nations is clearly below standards compared with developed countries.